Angina Symptom Burden Associated with Depression Status Among Veterans with Ischemic Heart Disease. Issue 1 (10th July 2014) - Trivedi, Ranak; Gerrity, Martha; Rumsfeld, John S.; Spertus, John A.; Sun, Haili; McDonell, Mary; Doak, Melanie; Lucas, Linda; Fihn, Stephan D.
Abstract: Background: Angina and depression are common in ischemic heart disease (IHD), but their association remains understudied. Purpose: This study was conducted in order to evaluate the association of 1 year change in depression with change in patient-reported outcomes of stable angina. Methods: Five hundred sixty-nine stable angina patients completed the Seattle Angina Questionnaire and Patient Health Questionnaire (PHQ) at baseline and 1 year. Participants were divided into four groups: not depressed, new onset of depression at 1 year, remitted at 1 year, and persistently depressed. Associations between depression and angina symptoms were evaluated using regression models. Results: Compared to those not depressed, newly depressed participants reported more angina ( β  = −11.7, p  < 0.001) and physical limitations ( β  = −11.8, p  < 0.001) and lower treatment satisfaction ( β  = −15.03, p  < 0.001) and quality of life ( β  = −15.4, p  < 0.001). Persistently depressed participants reported physical limitations ( β  = −7.4, p  < 0.05), lower treatment satisfaction ( β  = −10.1, p  < 0.001), and poorer quality of life ( β  = −10.03, p  < 0.001). Conclusions: Changes in depression scores and angina outcomes were significantly associated.